SURVEY PEMANFATAN REMPAH RIMPANG DI MASA PANDEMI COVID – 19 PADA MASYARAKAT KELURAHAN SUKA KARYA KECAMATAN KOTA BARU KOTA JAMBI - Rahmah Rahmah; Supriatna Supriatna; Sugiarti Sugiarti (NHM PRESS, 2023)
The Corona virus attacks millions of people regardless of caste, ethnicity, religion, age, gender and skin color. Efforts that can be made to avoid transmission of the corona virus are maintaining body immunity or endurance by consuming immune-boosting spices. The purpose of this study was to see what percentage of people use spices, especially Turmeric Rhizomes, Ginger Rhizomes and other Spices. This type of research is descriptive observational using a survey approach with a total target population of 7,923 people from 2,187 heads of families spread across 19 RTs and involving 370 respondents. Research data was collected by distributing questionnaires or questionnaires to respondents, then the research data was processed to obtain the frequency of each variable. The results showed that the utilization of Rhizome Spices during the Covid-19 Pandemic was the Utilization of Turmeric Rhizomes (37.30%), Ginger Rhizomes as much as 37.74% and the use of other spices 38.9%. The conclusion of the study is that in the Suka Karya Village community the use of rhizome spices is still low